On the growth of supersolutions of nonlinear PDE's on exterior domains. (November 2016) - Impera, Debora; Pigola, Stefano
Abstract: We obtain a comparison principle on annuli, with "catenoid-like" functions, for supersolutions of non-linear elliptic PDEs over exterior domains in a non-positively curved manifold with a pole. This result is applied to get an upper estimate on the growth of such supersolutions and, in particular, of exterior graphs of non-negative mean curvature.